Analisis Kesesuaian Penyelenggaraan Perpustakaan Sekolah Berdasarkan Standar Perpustakaan (Studi Kasus MIS Bojongmalang Pangandaran) - Nukhbatillah, Isyfi Agni; Hasanah, Uswatun; Suhertin, Tatin; Milah, Ai Robihatil; Setia Mukti, Ajeng Tanjiah (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
Abstract:. The library is one of the supporting components in an academic institution that plays an important role in providing books as a reference for learning. The function of the library itself is to provide services to users and increase reading enjoyment, as well as broaden the horizons and knowledge of students. The location of the MI Bojongmalang library is currently not strategic because it is in a hidden place, namely behind the school, near forests, gardens and now it is still in the renovation stage which has been neglected for a long time. the location is not strategic and seems haunted. The purpose of this research is to find out the ideal location of the school library building. This research is a qualitative research using observation, interviews and literature studies. The results of this study are that MIS Bojongmalang still requires continuous improvement and innovation efforts in the administration of libraries, especially in determining the location of library buildings and procuring shortages of other infrastructure facilities. Keywords: Library, Organization, Ideal Location.